Dysphagia therapy post stroke: An exploration of the practices and clinical decision-making of speech-language pathologists in Australia. (4th March 2018) - Jones, Olivia; Cartwright, Jade; Whitworth, Anne; Cocks, Naomi
Abstract: Purpose : A variety of dysphagia management options are available for the treatment of dysphagia following a stroke, however, it is unknown which of these approaches are most commonly utilised by Australian speech-language pathologists (SLPs) and whether particular factors influence decision-making. Method : The aim of this study was to investigate, through an online survey, the treatment practices of SLPs in Australia for the treatment of dysphagia post-stroke and identify the factors influencing treatment decisions. Result : A total of 118 SLPs completed the online survey. Descriptive statistics identified large variability in the dysphagia treatments utilised, with all 24 therapies listed in the online survey reported as being routinely used. Compensatory therapies were ranked as being utilised more frequently than rehabilitative approaches, with six of the seven highly utilised therapies being compensatory in nature. A client's cognitive capacity was the most prominent factor influencing SLPs' treatment decisions. Conclusion : This study provides insight into the practices of SLPs in Australia for the treatment of dysphagia following stroke and discusses potential for shifts in practice. It highlights the complexity involved in the decision-making process and that clinicians consider evidence, as well as client, clinician and service factors, when selecting between the range of options available.